Copies of resolutions adopted by the British trade union and labour movement, and the International Federation of Trade Unions and the Labour and Socialist International - Labour Party (Great Britain) ; International Federation of Trade Unions ; Labour and Socialist International
1937-09-06 017b-0032-009 292/946/17b/39(ix)